Non‐neutralizing epitopes induce robust hepatitis C virus (HCV)‐specific antibody‐dependent CD56+ natural killer cell responses in chronic HCV‐infected patients. (7th April 2017) - Long, L.; Jia, M.; Fan, X.; Liang, H.; Wang, J.; Zhu, L.; Xie, Z.; Shen, T.
Summary: Natural killer (NK) cell‐mediated antibody‐dependent cellular cytotoxicity (NK‐ADCC) is of considerable interest in viral infection. However, little is known about NK‐ADCC responses in chronic hepatitis C virus (HCV) infection. In this study, impaired non‐specific antibody‐dependent CD56 + NK cell responses were observed in chronic HCV infection, as shown by decreased degranulation (extracellular CD107a expression) and interferon (IFN)‐γ production in response to antibody‐bound P815 cells. A peptide pool composed of epitopes recognized by anti‐HCV‐E1/E2 antibodies could induce pronounced HCV‐specific antibody‐dependent NK cell responses in sera from approximately half the chronic HCV carriers. Additionally, HCV‐specific epitopes with the capacity to induce robust NK‐ADCC activity were identified. Five linear NK‐ADCC epitopes (aa211‐aa217, aa384‐aa391, aa464‐aa475, aa544‐aa551 and aa648‐aa659 of the HCV envelope) were identified and do not overlap with putative linear neutralizing epitopes. This study revealed the dysfunctional characteristics of antibody‐dependent CD56 + NK cell responses in chronic HCV carriers. The key non‐neutralizing NK‐ADCC epitopes identified in this study may act as new targets for immunological intervention. Abstract : A peptide pool composed of epitopes recognized by anti‐HCV‐E1/E2 antibodies could induce pronounced HCV‐specific antibody‐dependent NK cell responses in sera from approximately half of the chronic HCV carriers. Five linear NK‐ADCC epitopes were identified and do not overlap with putative linear neutralizing epitopes.